Sosialisasi Dan Aplikasi Elisitor Biosaka Pada Budidaya Tanaman Padi (Oryza Sativa) Di Desa Pudak, Kecamatan Kumpeh Ulu, Kabupaten Muaro Jambi, Provinsi Jambi - Dedy Antony; Lizawati Lizawati; Weni Wilia; Yulia Alia; Agus Kurniawan Mastur (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Efforts to increase rice (Oryza sativa) production by farming communities in Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency still partly depend on the use of inorganic fertilizers. An alternative to increasing production that is safe and environmentally friendly is the use of biosaccharide elicitors made from organic materials. This needs to be socialized to farmers regarding the use of biosaka made from weeds, some of which are still unknown to farmers in Pudak Village. This activity began with a discussion meeting with the head of the farmer group, the Plant Pest Organism Control Officer (POPT) to look at problems in the farmers' rice fields and continued with land observations. Then socialization was carried out to the community and continued with the practice of making biosaka and implementation in rice fields in Pudak Village. The results of this activity show that farmers are very enthusiastic about all activities from manufacture to application on the land. There were 45 participants who attended and were active until the end of the activity. The follow-up activities showed farmers practicing how to make it in their respective groups. The results of monitoring and evaluation have proven that the biosaka elicitor has been successfully produced by farmers independently as much as 30 L. The application results show a positive and better plant response compared to plots where biosaka was not applied.